High apolipoprotein E in cerebrospinal fluid of patients with Lewy body disorders is associated with dementia. Issue 5 (26th August 2013) - Vijayaraghavan, Swetha; Maetzler, Walter; Reimold, Matthias; Lithner, Christina Unger; Liepelt‐Scarfone, Inga; Berg, Daniela; Darreh‐Shori, Taher
Abstract: Apolipoprotein E ε4 allele ( APOE ε4) increases the apolipoprotein E (apoE) protein levels in Alzheimer's disease (AD) cerebrospinal fluid (CSF). Thus, we hypothesized that apoE levels were also associated with the APOE genotype, and amyloid‐β (Aβ)‐associated clinical, functional, and imaging parameters in patients with Lewy body‐associated disorders (LBD). Indeed, similar to AD, patients with LBD displayed high CSF apoE levels (greatest in patients with dementia with LBD), and this was linked to APOE ε4. High CSF apoE protein correlated positively with CSF soluble amyloid precursor protein, total tau, and cortical and striatal Pittsburgh compound B retention; and correlated negatively with CSF Aβ42, cognitive tests scores, and glucose uptake ratio in the temporal and parietal cortices. APOE ε4‐triggered accumulation of apoE in CSF is related to Aβ‐associated clinical and functional imaging parameters in LBD. Accordingly, therapeutic strategies aimed at reducing apoE levels in the brain should be explored not only in AD but also in LBD, particularly when accompanied with dementia.